PERAN KEPEMILIKAN MANAJERIAL SEBAGAI MEKANISME PENINGKATAN KUALITAS LABA DAN NILAI PERUSAHAAN - Fenny Putrianti; Sugi Suhartono (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
This research is aimed to determine the role of managerial ownership as a mechanism to improve the quality of earnings and value companies in manufacturing companies listed in the Indonesia Stock Exchange period 2014-2016. The sample in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in the period 2014-2016. The sample were selected by purposive sampling method, with the number of sample is 312 companies. The results showed that managerial ownership negatively affects firm value and managerial ownership does not affect the quality of profit but has a negative relationship. In addition, the results also show that the quality of earnings does not affect the value of the company but has a negative relationship. In addition, the quality of earnings does not affect the value of the company. Based on the analysis, the quality of earnings as intervening variable is not able to mediate the relationship between managerial ownership and firm value.